2008
DOI: 10.1111/j.1740-1461.2007.00117.x
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Analysis of the Impact of Liability Pressure on the Supply of Obstetrician‐Gynecologists

Abstract: Conventional wisdom within the medical community suggests that dramatic increases in professional liability insurance premiums cause physicians to relocate or discontinue their practices in high-cost states. We employed a mixed-effects model to investigate the effect of malpractice risk, as measured by insurance premiums and various tort reforms, on the number of obstetrician-gynecologists (OB/GYNs) in the United States between 1992 and 2002. The longitudinal research design examines state-year-level data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Malpractice insurance premiums for general surgeons and obstetrician-gynecologists were calculated using the MLM’s annual survey data via a two-stage weighting approach (Yang et al , 2008). 3 Severity of malpractice claims and malpractice insurance premiums were adjusted to 2007 U.S. dollars (U.S.…”
Section: Methodsmentioning
confidence: 99%
“…Malpractice insurance premiums for general surgeons and obstetrician-gynecologists were calculated using the MLM’s annual survey data via a two-stage weighting approach (Yang et al , 2008). 3 Severity of malpractice claims and malpractice insurance premiums were adjusted to 2007 U.S. dollars (U.S.…”
Section: Methodsmentioning
confidence: 99%
“…We model damages caps using 4 dummy variables (1 punitive damages cap and 3 levels of noneconomic damages cap). Because tort reforms tend not to affect the malpractice climate instantaneously, 33 we lag each tort-reform variable by 1 year from the date of its implementation. If a tort reform was subsequently held unconstitutional, its value is set to zero beginning in the year after the holding.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11][12][13] Other studies have found such relationships to be complex, weak, or nonexistent.…”
Section: Background On Defensive Medicinementioning
confidence: 99%